1998
DOI: 10.1136/gut.42.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Short segments of Barrett’s epithelium and intestinal metaplasia in normal appearing oesophagogastric junctions: the same or two different entities?

Abstract: Background-Endoscopic diagnosis of short segments of Barrett's epithelium (SSBE) is diYcult and its meaning in terms of the presence of specialised columnar epithelium (SCE) has not been prospectively evaluated. Aims-To evaluate the prevalence of SCE in patients with an endoscopic diagnosis of SSBE and in individuals with normal appearing oesophagogastric junctions, and to compare the clinical characteristics of these two groups. Patients-Thirty one patients with an endoscopic diagnosis of short Barrett's oeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 24 publications
1
46
1
3
Order By: Relevance
“…In this study, IM was found in 55% of patients with segments of esophageal columnar lining measuring 2 cm or less. This is similar to studies of other investigators 2,20,21 who found IM in 48% to 61% ofpatientssuspectedofhavingshort-segmentBarrettesophagus. Furthermore, our results suggest that the duration of GERD and the presence of duodenoesophageal reflux are important factors in the pathogenesis of IM.…”
Section: Commentsupporting
confidence: 80%
“…In this study, IM was found in 55% of patients with segments of esophageal columnar lining measuring 2 cm or less. This is similar to studies of other investigators 2,20,21 who found IM in 48% to 61% ofpatientssuspectedofhavingshort-segmentBarrettesophagus. Furthermore, our results suggest that the duration of GERD and the presence of duodenoesophageal reflux are important factors in the pathogenesis of IM.…”
Section: Commentsupporting
confidence: 80%
“…It is difficult to determine differences in the prevalence rate of IM in the true gastric cardia compared to metaplastic columnar epithelium in the distal esophagus because the protocols used in most studies are not able to distinguish these two regions accurately (42,53). However, the results of several studies have shown that the prevalence of IM is higher in patients who have longer lengths of mucosa composed of pure cardia-type mucous glands (8,9,17).…”
Section: Intestinal Metaplasia Of the Gastroesophageal Junction Regionmentioning
confidence: 86%
“…Up to one-third of patients without endoscopic evidence of BE who present for upper GI endoscopy show IM in the GEJ region (2,39,42,43,(51)(52)(53)(54). The wide variation in reported prevalence rates between various studies is due to a variety of factors, such as differences in endoscopic techniques with and without magnification endoscopy; with and without the application of acetic acid, with and without the application of vital dye biopsy protocols, and patient populations utilized, the precise location and number of biopsies (i.e., true gastric cardia vs metaplastic columnar epithelium in the distal esophagus) and differences in histologic detection methods.…”
Section: Intestinal Metaplasia Of the Gastroesophageal Junction Regionmentioning
confidence: 99%
“…In studies carried out by Spechler et al 24 and Nandurkar et al, 25 a relation between SSBE and GER was not found. On the contrary, studies by Johnston et al 23 Pereira et al 26 showed a significant relation between SSBE and GER. Although we did not find a relation between the presence of esophagitis and BE, nonerosive GER disease that cannot be detected during endoscopic examination may be an important factor in the development of BE.…”
Section: Discussionmentioning
confidence: 85%